2008
DOI: 10.4321/s1130-01082008000500005
|View full text |Cite
|
Sign up to set email alerts
|

Evolución en la epidemiología de la hemorragia digestiva alta no varicosa desde el año 1985 hasta 2006

Abstract: a significant increase in mean age over the years was detected. The most frequent cause of hemorrhage was duodenal ulcer followed by gastric ulcer. Of significance is an increase in the proportion of neoplasms above of vascular injuries in the later group as apposed to the earlier one. We found no significant difference in mortality between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
3
2
0
Order By: Relevance
“…In our analysis, rebleeding was encountered in 7.72% of cases, and surgery was needed in 3.22% of patients. The differences of rebleeding rate among studies may be the result of various proportions of patients receiving combined endoscopic hemostasis vs pharmacologic therapy[9,18-22]. Similar to other studies, rebleeding proved to be an independent predictor of death due to a bleeding episode in our research ( P < 0.001).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our analysis, rebleeding was encountered in 7.72% of cases, and surgery was needed in 3.22% of patients. The differences of rebleeding rate among studies may be the result of various proportions of patients receiving combined endoscopic hemostasis vs pharmacologic therapy[9,18-22]. Similar to other studies, rebleeding proved to be an independent predictor of death due to a bleeding episode in our research ( P < 0.001).…”
Section: Discussionsupporting
confidence: 86%
“…Our study reveals both differences and similarities compared to other similar research (Table 10)[1-17]. The age of patients may be the result of the age distribution of different populations[1,14,18]. In conformity with the literature, our results revealed that peptic ulcer represents the most common etiology of NVUDB (73% of cases)[7].…”
Section: Discussionsupporting
confidence: 81%
“…Our population has a mean age of 49 years with extremes ranging from 12 to 100 years. These data coincide with those described in the two series in the same endoscopic unit in 1982 and 1999 [9, 10], but they are different from those described in the literature, where the mean age was between 58 and 73 years [5, 8, 1113]. This can be explained by the youth of the Moroccan population.…”
Section: Discussionsupporting
confidence: 85%
“…They can appear more frequently in the elderly population [13]. In the present study, 12% of patients had a history of a previous bleeding.…”
Section: Discussionmentioning
confidence: 54%
“…Gastrointestinal angiodysplasia was found in 75 endoscopies, 55 gastric and 25 duodenal, and an AB rate of 18.2% and 57.4% respectively. Dieulafoy’s lesion was described in 23 patients, 15 gastric and 8 duodenal, and an AB rate of 80% and 50% each 1 2 .…”
mentioning
confidence: 99%